Long cryopreserved lab-adapted Plasmodium falciparum increases resistance to chloroquine but not its susceptibility - Pua, Jing Yit; Abu Bakar, Nurhidanatasha; Nik Kamarudin, Nik Abdul Aziz; Ghazali, Siti Zulaiha; Khairul Mohd Fadzli Mustaffa (Life Sciences, Medicine and Biomedicine, 2020)
Introduction: Plasmodium falciparum (P. falciparum) is a deadly protozoan that is accountable for malaria and chloroquine was the first-line antimalarial drug before its withdrawal and replaced by artemisinin. To date, several studies showed that P. falciparum had regained its sensitivity towards chloroquine after its withdrawal for decades. By understanding the basic principle and mechanism of chloroquine resistance in P. falciparum, at the molecular level, it would be valuable prior to the re-introduction of chloroquine as a first-line anti-malarial drug for malaria treatment. Thus, this study was conducted to determine the chloroquine resistance level of long preserved lab-adapted P. falciparum strain. Methodology: By using 14 years (2006-2020) cryopreserved chloroquine-sensitive (3D7) and chloroquine-resistant (W2) lab-adapted P. falciparum strains, the strains were subjected to continuous culture for three months before in vitro drug susceptibility assay and single nucleotide polymorphisms (SNP) analysis on Pfcrt and Pfmdr-1 gene for both strains. Results: This study shows the IC50 chloroquine of lab-adapted P. falciparum 3D7 and W2 strains were at 32.98 nM and 691.21 nM, respectively and both strains showed 3-fold higher IC50 when compared to their susceptibility before cryopreserved (3D7; 13.84nM and W2; 208.27 nM). The SNPs result showed a consistent amino acid substitution at position 76 (K to T) on PfCRT and 86 (N to Y) in Pfmdr-1 gene which concordance with other studies before preservation. Conclusion: Thus, this study shows that long cryopreserved of lab-adapted P. falciparum increases the chloroquine resistance level but not exhibited any change in susceptibility.